Ultrasound Features of Fetal Anemia Lessons From Hemoglobin Bart Disease - Keooudone Thammavong (2020)
© 2020 American Institute of Ultrasound in Medicine Insights gained from this review are as follows: (1) Ultrasound is highly effective in early detection of fetal hemoglobin (Hb) Bart disease. (2) The most sensitive parameters in predicting Hb Bart anemia appear to be the cardiac diameter–to–thoracic diameter ratio, middle cerebral artery peak systolic velocity, and placental thickness. (3) Several other ultrasound markers are helpful in increasing specificity, such as hepatosplenomegaly. (4) Hydrops fetalis is not a consequence of heart failure but rather of hypervolemia and high vascular permeability of fetuses, whereas heart failure is a very late consequence of a long-standing overworked heart. (5) Management guidelines for fetuses at risk of Hb Bart disease are proposed.